Genetic adult lactase persistence is associated with risk of Crohn's Disease in a New Zealand population - Nolan, Deborah J (BioMed Central, 2010)
BACKGROUND: Mycobacterium avium subspecies paratuberculosis (MAP) is an infective agent found in ruminants and milk products, which has been suggested to increase the risk of gastrointestinal inflammation in genetically susceptible hosts. It is hypothesized that lactase persistence facilitates exposure to such milk products increasing the likelihood of adverse outcomes. Individuals either homozygous or heterozygous for the T allele of DNA variant, rs4988235, located 14kb upstream from the LCT locus, are associated with having lactase persistence. The aim of this study was to determine whether lactase persistence as evident by the T allele of rs4988235 is associated with Crohn's Disease (CD) in a New Zealand population. FINDINGS: Individuals homozygous for the T allele (T/T genotype) showed a significantly increased risk of having CD as compared with those homozygous for the C allele (OR = 1.61, 95% CI = 1.03-2.51). Additionally, a significant increase in the frequency of the T allele was observed in CD patients (OR = 1.30, 95% CI = 1.05-1.61, p = 0.013), indicating that the T allele encoding lactase persistence was associated with an increased risk of CD. CONCLUSIONS: Our findings indicate that lactase persistence as evident by the presence of the T allele of rs4988235 is associated with risk of CD in this New Zealand Caucasian population.